(untitled) (Damu Journal of Sport Sciences, 2025)
The importance of the study is evident in finding a new (proposed) test through which the most accurate results can be obtained in evaluating the most important defensive skills and placing this test in the hands of workers, specialists and experts in the field of testing and training in sports institutions and clubs as central and sub-unions throughout the country. The researchers conducted an experiment on some of these tests (previous tests) that depend on the evaluation of arbitrators and (new (proposed) tests that depend on time as a real and objective criterion for it, and through analyzing many matches for the game of Kabaddi to know the most important defensive skills used frequently in these matches and at a very high rate ranging between (90-100%) in these matches. Therefore, the researchers decided to prepare and design new tests for the most important defensive skills in the game of Kabaddi, in line with the modernity of the tests as an evaluation and training on them and the high ability to master these skills to reach the best level of skill, and to obtain more accurate results in a shorter time, The study objectives were to design tests for the most important defensive skills in the game of Kabaddi, and to compare the results of previous tests and the proposed tests in measuring the most important defensive skills in the game of Kabaddi. As for the hypotheses, there was a discrepancy between the previous tests and the proposed new tests for the most important defensive skills in the game of Kabaddi. The previous tests and the proposed tests have the ability to distinguish between the testers in measuring the most important defensive skills in the game of Kabaddi, and the best are the new (proposed) tests due to the nature of the similar work in the course of the game. The research community included the youth players and applicants to the Al-Daghara Sports Club for the year (2025), numbering (60) players,The test was conducted on a sample of (50) players representing a percentage of the research community (%83.333), while (10) players did not undergo this test for reasons beyond their control, such as illness and other occupations. The researchers conducted homogeneity in the variables (height, weight, age, and training age) because they are considered variables that have a direct or indirect impact on the most important defensive skills in the game of Kabaddi. All field procedures were implemented, including tests and measurements, through which the necessary data was obtained, and then appropriate statistics were conducted, tabulated, analyzed, discussed, and appropriate conclusions and recommendations were made from the achieved results.